2020
DOI: 10.3390/ijerph17207568
|View full text |Cite
|
Sign up to set email alerts
|

The Design, Content and Delivery of Relationship and Sexuality Education Programmes for People with Intellectual Disabilities: A Systematic Review of the International Evidence

Abstract: There is growing empirical evidence regarding the relationship and sexuality experiences and needs of children, young people and adults with intellectual disabilities. A total of twelve papers met the inclusion criteria regarding relationship and sexuality education (RSE) programmes specific to the needs of this population. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines were followed and quality appraisal undertaken. The four themes identified were principles informi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 59 publications
0
27
0
3
Order By: Relevance
“…Parental cooperation may facilitate the delivery of SE to children with IDs from home to school. Previous research has shown that implementing SE to students with disabilities is difficult to accomplish without active or passive parental participation [37,38]. According to Chai Tin and Lay Wah (2019), this scenario is different in Malaysia, where teachers stick to the ministry of education guidelines based on the current curriculum without engaging parents [32].…”
Section: Discussionmentioning
confidence: 99%
“…Parental cooperation may facilitate the delivery of SE to children with IDs from home to school. Previous research has shown that implementing SE to students with disabilities is difficult to accomplish without active or passive parental participation [37,38]. According to Chai Tin and Lay Wah (2019), this scenario is different in Malaysia, where teachers stick to the ministry of education guidelines based on the current curriculum without engaging parents [32].…”
Section: Discussionmentioning
confidence: 99%
“…Future research is thus needed to further elaborate on the attitudes of these groups. In light of the crucial role played by support staff and relatives in the provision of sex education and support [69], the authors have selected three implications that will be elaborated on below.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, due to the inclusion and exclusion criteria, results on sex education and support only pertained to adults with intellectual disabilities. This limitation is relevant in light of the conclusions from Brown et al [69], according to which the majority of education developed for people with intellectual disabilities is targeted toward children and youths.…”
Section: Discussionmentioning
confidence: 99%
“…2019; Brown et al . 2020). These reviews have suggested that existing RSE programmes lack specific outcome goals and that outcomes measured are heterogeneous (e.g.…”
Section: Introductionmentioning
confidence: 99%